Membangun karakter positif: Peran pendidikan karakter dalam perkembangan sosial emosional anak - Shidqiyyah, Elsya Iftitahus (Maliki Interdisciplinary Journal, 2024)
This article explores the important role of character education in building a child’s positive character. Character education is aimed at instilling moral and ethical values, which form the basis of a child’s social interaction. With character education, children are taught empathy, honesty, responsibility, and cooperation, which are fundamental to healthy social-emotional development. Schools and teachers, along with parents, have an important role to play in creating an environment that supports these positive values. Research shows that character education can improve a child’s social skills, emotional management, and self-confidence. This article highlights various methods of character education and underscores the importance of character education in shaping a harmonious and ethical society.